The EOLES project Remote Labs across the Mediterranean - Fidalgo, André Vaz (2014)
This paper describes the concept, methodology and first steps of an EU supported TEMPUS project EOLES (Electronics and Optics e-Learning for Embedded Systems). Its aim is the creation of a 3rd year Bachelor degree that relies exclusively on e-learning and remote laboratories. The project involves 15 institutions from four European countries and three North African countries. The proposed course will be run from several institutions simultaneously and should be accredited as a formal specialization year in all partner institutions, awarding 60 ECTU (European Transfer Credit Units). The course will integrate a Virtual Learning Environment and a Distributed Laboratory.